Coronary plaque burden, plaque characterization and their prognostic implications in familial hypercholesterolemia: A computed tomographic angiography study. (January 2021) - Pérez de Isla, Leopoldo; Alonso, Rodrigo; Gómez de Diego, José Juan; Muñiz-Grijalvo, Ovidio; Díaz-Díaz, José Luis; Zambón, Daniel; Miramontes, José Pablo; Fuentes, Francisco; de Andrés, Raimundo; Werenitzky, José; Padró, Teresa; Saltijeral, Adriana; et al.
Abstract: Background and aims: Heterozygous familial hypercholesterolemia (FH) is associated with premature atherosclerotic cardiovascular disease. Semi-automated plaque characterization (SAPC) by coronary computed tomographic angiography (CTA) provides information regarding coronary plaque burden and plaque characterization. Our aim was to quantify and characterize the coronary plaque burden of patients with FH using SAPC analysis and to identify which factors are related to plaque burden and plaque characteristics. A second aim was to analyse the prognostic implications of these parameters. Methods: Two hundred and fifty-nine asymptomatic individuals with molecularly determined FH were enrolled in this follow-up cohort study and underwent a coronary CTA analysed with SAPC. Results: Mean follow-up time after coronary CTA was 3.9 ± 2 years. Mean age was 46.9 (10.7) years (130 women, 50.2%). Median plaque burden was 25.0% (19.0–29.0), non-calcified plaque burden 22.83% (17.94–26.88), calcified plaque-burden 1.12% (0.31–2.86) and CCS 8.9 (0–93). Five-year risk was independently related to plaque burden, non-calcified plaque burden, calcified plaque burden and coronary calcium score (B:3.75, 95%CI:2.92–4.58; p < 0.001, B:2.9, 95%CI:2.15–3.66; p < 0.001, B:0.75, 95%CI 0.4–1.1; p < 0.001 and B:82.2, 95%CI:49.28–115.16; p < 0.001 respectively). During follow-up, there were 15 (5.81%) nonfatal events and 1 (0.4%) fatal event. Plaque burden was significantly related to event-free survival during follow-up (HR:1.11; 95%CI:1.05–1.18; p < 0.001). Conclusions: Coronary atherosclerosis and its qualitative components may be quantified by means of SAPC in patients with FH. Plaque burden, calcified plaque burden and non-calcified plaque burden were independently related to the estimated cardiovascular risk. Plaque burden was also related to prognosis. Graphical abstract: Image 1 Highlights: Coronary atherosclerosis burden may be quantified and plaque characteristics analysed in the coronary artery tree using coronary CTA in patients with familial hypercholesterolemia (FH). Coronary atherosclerosis, beyond coronary calcium, is highly prevalent in asymptomatic patients with FH. By means of coronary CTA, we can study every component of the coronary atherosclerotic plaque. Plaque burden, calcified plaque burden and non-calcified plaque burden are independently related to the cardiovascular risk and cardiovascular prognosis. This new diagnostic approach might improve the risk re-stratification and management optimization, allowing more personalized lipid lowering treatment, such us the use of PCSK9 inhibitors.